The Last Day and Brexit: Delusions of Future Past - Jajszczok, Justyna (Porównania, 2021)
The paper aims to show how the traditions of science fiction and, above all, invasion literature provide the ideological background for reading Andrew Hunter Murray’s The Last Day as a novel about Brexit. As it draws on anxious visions of the future, in which the enemy lurks around every corner, and the only salvation is complete isolation from the world, Murray’s work is read here as a Brexit dream come true, in which Britain is once again great, independent and uncontaminated by foreign elements. By evoking the myths that focus only on glory and conveniently “forget” the dark sides of the empire, the novel demonstrates that the fantasies of the past are as distant as the fantasies of the future; the loss of the world that never was is reworked in The Last Day into the loss of ecologically viable planet.